Literature Review on the Effect of Reward System and Work-Life Balance on Teacher Retention with Job Satisfaction as an Intervening Variable - Ritawati Sirait; Donalson Silalahi (Jurnal Multidisiplin Sahombu, 2026)
Teacher retention is a strategic issue in human resource management in the education sector, especially in private schools that face the challenge of high levels of educator transfer. Teacher stability has a great influence on the sustainability and quality of the learning process. Therefore, this study aims to systematically examine the influence of the reward system and work-life balance on teacher retention with job satisfaction as an intervening variable based on relevant literature reviews. The method used in this study is a literature review, by analyzing various national and international journals that discuss the reward system, work-life balance, job satisfaction, and teacher retention. The articles reviewed were selected based on the relevance of the topic, the credibility of the source, and the suitability of the research context in the field of human resource management, especially in educational organizations. The results of the literature review show that the reward system and work-life balance have a positive influence on teacher job satisfaction. Job satisfaction further plays an important role in increasing teacher retention. In addition, job satisfaction has been shown to mediate the relationship between the reward system and work-life balance on teacher retention. These findings indicate that human resource management policies that are oriented towards teacher welfare and satisfaction can strengthen teachers' decisions to stay in educational organizations. Theoretically, this study enriches the study of human resource management by placing job satisfaction as an intervening mechanism in the teacher retention model. Practically, the results of the research are expected to be the basis for school managers to design a reward system and work policies that support work-life balance to increase teacher satisfaction and retention in a sustainable manner.